Suggested Family Issues that are not Dealt with in Jordanian Personal Status Law No. (15/2019) in Marital Expenses: Legal Jurisprudential Study - Abu Hassan, Johayna Abd Al-Rahman Nemer; Arabiyat, Wael Mohammad (Dirasat: Shari’a and Law Sciences, 2023)
Objectives: This study aims to clarify some of the issues dealt with the jurisprudential books and not addressed by the amended Jordanian Personal Status Law and to propose legal texts for these issues. Methods: This study relied on the inductive approach by extrapolating and tracing the jurisprudential books in the four schools of thought and modern references, in addition to the legal materials related to the field of study. In addition, the study adopted the analytical approach by analyzing the sayings and inferences of jurists related to the subject of study. Results: The husband is obliged to pay for the wife’s treatment and provide alimony during the period of illness, even if she cannot do her marital duties , since the wife is considered to be his partner for which he is responsible. The study also revealed that the wife must be provided with alimony during her stay at the matrimonial home. In addition, the results demonstrated that the husband does not have the right to prevent the wife’s family from visiting her in the matrimonial home and that the husband may stay with the wife during the waiting period if the divorce is of retrogressive type. Conclusions: The proposed issues shall be submitted to the Jordanian Judge of Justice Chamber to be included in an explicit provision when amending the Jordanian Personal Status Law and to study other issues that are not addressed in the other sections.